STATISTICAL ANALYSIS IN SELECTING THE BEST ELECTRODE BETWEEN ALUMINUM AND IRON IN TSS REMOVAL USING ELECTROCOAGULATION - Mindriany Syafila; Muhammad Sonny Abfertiawan; Marisa Handajani; Faiz Hasan; Hanifah Oktaviani; Nur Novilina Arifianingsih (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
Indonesia is a country that has considerable coal reserves with coal resources of 149.01 billion tons. One of the problems of coal mining is turbidity. The turbidity is caused by the excavation of the open pit mine so that rainwater contact with the main wall. So that mud is formed, which can increase turbidity levels. The concentration of Total Suspended Solids (TSS) due to this phenomenon reaches 5,400 mg/L. Aim: This study aims to set aside TSS by electrocoagulation processing method using a batch system with eight pairs of iron electrodes arranged monopolarly. Methodology and Results: Comparisons using statistically independent t-tests showed that there was no significant difference between the iron and aluminium electrodes in the pH parameter. Conclusion, significance, and impact study:There were significant differences between iron and aluminum electrodes in the parameters of TDS and TSS. In the measured TDS and TSS parameters, the electrocoagulation process using iron electrodes has a higher value than aluminum electrodes. In the TSS removal, there is no significant difference between the two electrodes (iron and aluminium).